Factors That Influence Blood Pressure in 3- to 5-Year-Old Children: A Pilot Study. Issue 1 (January 2018) - Rice, Marti; Turner-Henson, Anne; Hage, Fadi G.; Azuero, Andres; Joiner, Cynthia; Affuso, Olivia; Ejem, Deborah; Davis, Sara Laubinger; Soistmann, Heather
While incident elevations in blood pressure (BP) are apparent in preschool years, factors influencing BP in this population have received little attention. The purposes of this pilot study were to determine the feasibility of collecting data from preschoolers and their mothers and to determine effect sizes of relationships between BP and sex, race, birth status, body mass index (BMI), waist circumference (WC), geographic location, serum C-reactive protein (CRP), and salivary cortisol (morning, afternoon). A hypothesis-generating correlational design was used; 56 children, aged 3–5 years, were enrolled from six rural and urban Head Start programs in a southeastern state. On Day 1 of data collection, mothers completed demographic questionnaires and children had blood drawn by finger stick. On Day 2, children gave saliva samples for cortisol, were measured for height by stadiometer, weight by digital scales, and WC by tape measure and had their BP measured by Dinamap. Incident elevations in BP were found in 30% of children (17/56), the majority of which were of systolic BP; 65% of those with elevations were of normal weight. Data collection was feasible with few problems. Small-to-medium effect sizes were noted for BP status (normal, prehypertensive, and hypertensive) and cortisol p.m. and birth status (parent-reported prematurity or term); small effect sizes were seen for BP status and BMI, race, sex, and geographic location. CRP and cortisol had medium- and small-to-medium effect sizes, respectively, with diastolic blood pressure. Studies with larger, more diverse samples need to be conducted to test hypotheses posited from these estimated effect sizes.